Pengaruh Kompetensi dan Beban Kerja Terhadap Kinerja Karyawan pada Dinas Ketahanan Pangan dan Pertanian Kota Bogor - Muhammad Sofa; Adriza Adriza; Yuni Pratikno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of competence and workload on employee performance at the Bogor City Food and Agriculture Security Agency, this study uses a quantitative research method, using saturated samples where the sample in this study is the entire population with a total of 65 respondents, data collection techniques using questionnaires and data analysis techniques using Research Instrument Test analysis techniques which are divided into Validity tests and Reliability tests. Classical Assumption Tests which are divided into Normality tests, Multicollinearity tests, Autocorrelation tests and Heteroskesdasrisity tests. Hypothesis Tests which are divided into Individual Parameter Significance Tests (T Statistical Tests), Simultaneous Tests (F Statistical Tests) and Results from the study of variable X1 are known to be independent variables of employee competence on average of 3.01, variable X2 independent variables of workload on average of 2.95 and variable Y dependent variables of performance on average of 2.91. The research results show that variable X1 has a positive and significant influence between the competency variable and employee performance, with a coefficient value of 0.00 <0.05. Variable X2 has a positive and significant influence between the workload variable and employee performance, with a coefficient value of 0.00 <0.05. Variable Y shows that simultaneously, competency and workload have a positive and significant influence on employee performance, as evidenced by a significance value of 0.00 <0.05..